Nonlinear and Linear PID Controllers-Based Hybrid Flight Control Strategy for a Quadcopter With Slung Load - Abhishek Manalathody; Kishoor Santhana Krishnan; Jisnu Adindtra Subramanian; Sakthivel Thangavel; Jinraj V. Pushpangathan; Hariprasanth Paranjothy (IEEE Access)
This paper proposes a new hybrid flight control strategy for a quadcopter with a slung load to achieve a user-defined trajectory following. The high-fidelity coupled nonlinear model involving the quadcopter and slung load is obtained by integrating the nonlinear slung load model with the nonlinear quadcopter model. The quadcopter’s nonlinear model is derived using the Euler-Newton method, whereas the slung load model is obtained using the Lagrangian methodology. The hybrid flight control strategy for this quadcopter with a slung load to accomplish trajectory tracking is developed using a conventional three-loop flight control structure. This control structure uses both linear proportional-integral-derivative (LPID) and nonlinear PID (NLPID) controllers. Here, NLPID controllers are employed in the outer loop for accomplishing trajectory tracking, whereas LPID controllers are used in the inner and middle loops to maintain stability and attitude tracking, respectively. Furthermore, the proposed technique uses a dedicated linear proportional-derivative controller to track the relative slung load positions with respect to the center of the quadcopter, thus reducing the adverse effect of the slung load oscillations. The effectiveness of the new hybrid flight control strategy is verified through different 8 degree-of-freedom (DOF) nonlinear numerical simulations.